Proceedings of the 6th ACM SIGCOMM Conference on Internet Measurement 2006
DOI: 10.1145/1177080.1177087
|View full text |Cite
|
Sign up to set email alerts
|

Finding diversity in remote code injection exploits

Abstract: Remote code injection exploits inflict a significant societal cost, and an active underground economy has grown up around these continually evolving attacks. We present a methodology for inferring the phylogeny, or evolutionary tree, of such exploits. We have applied this methodology to traffic captured at several vantage points, and we demonstrate that our methodology is robust to the observed polymorphism. Our techniques revealed non-trivial code sharing among different exploit families, and the resulting ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…By manually inspecting some of the shellcodes with same or similar lengths, but different MD5 hashes, we observed that in most cases the actual payload code was the same, but the seeding URL or IP address from where the "download and execute" shellcode would retrieve the actual malware was different. Our results are in accordance with previous studies [17] and clearly show that polymorphic shellcodes are extensively used in the wild, although in most cases they employ naive encryption methods, mostly for concealing restricted payload bytes.…”
Section: Real-world Deploymentsupporting
confidence: 93%
“…By manually inspecting some of the shellcodes with same or similar lengths, but different MD5 hashes, we observed that in most cases the actual payload code was the same, but the seeding URL or IP address from where the "download and execute" shellcode would retrieve the actual malware was different. Our results are in accordance with previous studies [17] and clearly show that polymorphic shellcodes are extensively used in the wild, although in most cases they employ naive encryption methods, mostly for concealing restricted payload bytes.…”
Section: Real-world Deploymentsupporting
confidence: 93%
“…Ma et al [18] used code emulation to extract the actual runtime instruction sequence of shellcode samples captured in the wild. Spector [11] uses symbolic execution to extract the sequence of library calls made by the shellcode, along with their arguments, and at the end of the execution generates a low-level execution trace.…”
Section: Related Workmentioning
confidence: 99%
“…Excellent, comprehensive reference material on malware can be found in [26]. Ma et al present a study more closely related to our own that infers the phylogeny (i.e., behavior characteristics) of malware shellcode [16]. Our work is most similar to these studies in that we too aim to establish evolutionary relationships between malware.…”
Section: Related Workmentioning
confidence: 72%
“…First, we hope to expand the corpus of malware meta-data in order to flesh out the evolutionary characteristics of malware in greater detail. Second, we believe that adding the behavioral characteristics such as those identified in [16] and others will further enrich our analysis. Finally, we will work more closely with AV companies and others concerned with malware analysis, to develop methods for anticipating future trends in malware development.…”
Section: Discussionmentioning
confidence: 99%